The Self Exitated Induction Generator with Observation Magnetizing Characteristic in The Air Gap - Ridwan Gunawan; Feri Yusivar; Budiyanto Budiyanto (Institute of Advanced Engineering and Science, 2015)
This paper discusses the Self Exitated induction Generator (SEIG) by approaching the induction machine, physically and mathematically which then transformed from three-phase frame abc to-axis frame, direct axis and quadratur-axis. Based on the reactive power demand of induction machine, capacitor mounted on the stator of the induction machine then do the physical and mathematical approach of the system to obtain a state space model. Underknown relationships, magnetization reactance and magnetizing current is not linear, so do mathematical approach to the magnetization reactance equation used in the calculation. Obtained state space model and the magnetic reactance equation is simulated by Runge kutta method of fourth order. The equation of reactance, is simulated by first using the polynomial equation and second using the exponent equation. The load voltage at d axis and q axis using the polynomial laggs 640µs to the exponent equation. The polynomial voltage magnetitude is less than 0.6068 volt from the exponent voltage magnitude